ANALYSIS OF CRUCIAL VARIABLES FOR THE SUSTAINABLE DEVELOPMENT OF RED RICE CULTIVATION IN JATILUWIH VILLAGE, TABANAN REGENCY - Made Ayu Vivi Lianita; Ida Ayu Nyoman Saskara (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study focuses on identifying the crucial variables that contribute to the sustainability of red rice cultivation, with the research conducted in Jatiluwih Village, Tabanan Regency. Crucial variables were identified through Focus Group Discussions (FGDs) involving 19 stakeholders and were further validated using questionnaires distributed to 30 respondents as a control measure against the FGD findings. The collected data were analyzed using the MICMAC method (Matrix of Cross-Impact Multiplications Applied to Classification) to determine the variables that influence and/or depend on the sustainability of red rice farming. The analysis results identified several key variables among the 11 assessed, including input prices (production facilities), social capital, availability of agricultural labor, and traditional agricultural rituals.